Eksistensi Etika Politik Islam dalam Pemerintahan - Nurul Azisah Syahrani Haris; Andi Muh Reza Caecar Arfan; Andi Muhammad Aflah; Kurniati Kurniati (Lembaga Pengembangan Kinerja Dosen, 2024)
Ethics is a field of philosophy that discusses the moral principles that govern humanbehavior, while politics deals with decision-making and the management of power in society. In Islam, political ethics is a concept that regulates human relationships in the political world.Islamic political ethics consists of a collection of moral values and principles that should guide everyone involved in political activities, both as citizens and leaders. Islamic political ethics has a strong relevance in the context of politics and governance. The moral values in Islam can serve as guidelines for leaders and citizens in building a better society. Despite the challenges faced, ongoing efforts to implement Islamic political ethics are considered essential in building an ideal and ethical government. It is important to build a just, prosperous, and moral society through the application of Islamic political ethics, which includes principles such as justice,equality, democracy, deliberation, freedom, and respect for the rights of others. In addition, this journal reviews the methods Ali Shari'ati used to make his assertions about the importance of Islam as a basic political ethic. A just, moral, and prosperous government can be achieved through the application of Islamic political ethics. Political ethics is not a convoluted system, but rather a number of noble values that are in line with the principles of Islam.